Adhering to COVID-19 health guidelines: A behavioral-failure perspective - Rusou, Zohar; Diamant, Irene (Frontiers in Psychology, 2022)
The mitigation of pandemics like that caused by the current COVID-19 virus is largely dependent on voluntary public adherence to government rules and regulations. Recent research has identified various individual covariates that account for some of the variance in compliance with COVID-19 behavioral guidelines. However, despite considerable research, our understanding of how and why these factors are related to adherence behavior is limited. Additionally, it is less clear whether disease-transmitting behaviors during a pandemic can be understood in terms of more general behavioral tendencies. The current research has examined the utility of a behavioral-failure lens in predicting adherence to COVID-19 guidelines and in illuminating mechanisms underlying the previously established relationship between Conscientiousness and adherence. In the two studies reported here, individual variations in the predisposition to behavioral failures predicted adherence to COVID-19 measures, and mediated the relationships between Conscientiousness and adherence. The Failure Proneness (FP) questionnaire predicted compliance with COVID-19 guidelines, while the Cognitive Failure Questionnaire (CFQ) did not. The results of hierarchical regressions showed that COVID-19 behavior was predicted only through the intentional factors (and mainly by Noncompliance-Violations). Hence, our data lends support to the notion that noncompliance with official COVID-19 prevention guidelines is driven mainly by intentional factors related to violation of norms and rules. The theoretical and practical implications of this finding are discussed.